Evaluation of different rhodium modifiers and coatings on the simultaneous determination of As, Bi, Pb, Sb, Se and of Co, Cr, Cu, Fe, Mn in milk by electrothermal atomic absorption spectrometry - Freschi, Gian Paulo G. [UNESP]; Freschi, Carolina D. [UNESP]; Neto, Jose A. Gomes [UNESP] (Springer Wien, 2008)
Different kinds of modifiers and coatings on the integrated platform of transversely heated graphite atomizer (THGA) have been tested for the simultaneous determination of two group of elements: the first, the more volatile, formed by arsenic, bismuth, lead, antimony and selenium; the second, the less volatile, formed by cobalt, chromium, cupper, iron and manganese in milk by electrothermal atomic absorption spectrometry. Different Rh-modifiers were studied, such as Rh-coated platforms (Rh), carbide plus rhodium coated platforms (W-Rh, Zr-Rh), carbide-coated platforms (W and Zr) with co-injection of RhCl3, solutions and uncoated platforms with injection of solutions of Pd(NO3)(2), Mg(NO3)(2), and RhCl3. Milk samples were diluted 1:10 in 1.0% HNO3 and injected into the tube. The mass of modifier deposited and co-injected in the tube and the use of end capped tubes were also evaluated in order to improve the electrothermal behavior of analytes. Integrated platform pretreated with W plus co-injection RhCl3 for first group and pretreated with W-Rh for second group were elected. For 20 mu L injected samples the analytical curves in the 5.0-20.0 mu g L-1 concentration range have good linear correlation coefficients (r > 0.998). Relative standard deviations (n = 12) are < 6% and the calculated characteristic masses are between 5 pg and 62 pg.
Keywords: milk; simultaneous determination; ETAAS; rhodium; modifiers